Rooftop rainwater harvesting: An innovative approach towards resource conservation - Sahu, Raghubar; Kumar, Dharmendra; Sohane, R K; Kumar, Rakesh (Indian Farming, 2023)
Rainwater harvesting system (RWS) is also known as rainwater collection system or rainwater catchment system technology that collect and stores rainwater for human and livestock use. RWS range from simple rain barrels to more elaborate structures with pump, well, tank and purification system. Rainwater harvesting significantly contributed to cause of ecological and environmentalpreservation. By capturing and storing runoff, which can immediately reduce soil/water erosion, rainwater harvesting is itself a valuable strategy for soil and water conservation. Ground water recharge is the main objective of this technology. By ground water recharging, irrigation water is sufficient for raising crops and production increases. Actual demand will depend on several lifestylechoices.